Structure of human serum lipoproteins inferred from compositional analysis. - Shen, B W (1977)
Analysis of the correlations between size and chemical composition of lipoproteins of normolipidemic human plasma shows that the structure of all circulating lipoproteins is consistent with a spherical model of radius r in which a spherical liquid core of cholesterol esters and triglycerides of radius = r --20.2 A is surrounded by a monolayer of cholesterol and phospholipids with closely hydrophobic ends on the surface of the core. The average molecular areas at this inner surface are Spl = 68.5 A2/molecule for phospholipids and Sc= 39.1 A2/molecule for cholesterol. The proteins are closely packed with the hydrophilic head groups of phospholipids at the outer surface of the particle, with S' pl = 62.7 A2/molecule for phospholipids and Saa = 15.6 A2/amino acid for proteins. The polar head group of free cholesterol does not participate in the packing of the outer layer and thus must be masked by proteins. Free cholesterol is distributed among the circulating lipoproteins--with the exception of very high density lipoprotein and perhaps chylomicrons--according to a thermodynamic equilibrium governed by the curvature of the surface of the particle.